Training teachers in maintaining equity in the micro-moments of a mathematical dialogue. (January 2020) - Ramis-Conde, Ignacio; Hope, Alexander
Abstract: This article presents the analysis of a large body of video data of trainee teachers who were learning mathematical dialogue techniques. We explore some of the ways in which trainee teachers can make better use of children's own contributions to foster learning and increase pupil motivation – taking a number of analytic principles from conversation analysis. While the importance of dialogue in mathematics education has drawn increased attention in recent years, there is still relatively little work on how teachers may learn to make better use of dialogue in the classroom. This paper aims to address that lacunae. Highlights: Shows how trainee teachers manage small group teaching in different ways. Identifies different styles of trainee-teacher interaction with pupils. Provides suggestions on how to help pre-service teachers maintain equity. Shows how spaces to construct understanding may be managed in maths education.